PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN REPRODUKSI REMAJA TERHADAP PENGETAHUAN TENTANG PERILAKU SEKSUAL - Widiyanto, Budi; -, Purnomo; Sari, Arum Muria (Jurnal Keperawatan Komunitas, 2013)
Adolescents experience emotional and physical changes along their growth and development. Furthermore adolescents need information in order to adapt to these changes. As a result of the lack of information about everything that happens allows teens to fall into things that harm themselves, other people, and their families. The results of a preliminary survey on sexual behavior in Cepogo Village, Jepara indicates that 26.6% of adolescents knowledgeable good, 26.6% of adolescents were knowledgeable, and 46.6% are less knowledgeable. The purpose of this study was to determine the effect of adolescent reproductive health education toward adolescent knowledge of sexual behavior in Cepogovillage, Jepara. The method used in this study was the quasy experimental which seeks to discover causal relationships in a way involving a control group and experimental group. As for the sampling technique is the multistage sampling. This studyÂ using t-test analysis in finding the influence of adolescent reproductive health education toward adolescentsâ knowledge about sexual behavior. Results of this studyindicate that there is an effect of adolescent reproductive health education on knowledge about sexual behavior demonstrated by t count (8.037) is greater than the t table 1.668. The conclusion of this study is there is an effect of adolescent reproductive health education for adolescent knowledge of sexual behavior in Cepogo.